2016
DOI: 10.5152/dir.2016.15475
|View full text |Cite
|
Sign up to set email alerts
|

Günther Tulip inferior vena cava filter retrieval using a bidirectional loop-snare technique

Abstract: Inferior vena cava (IVC) filters are an effective means to prevent pulmonary embolism in the setting of a contraindication to anticoagulation. Their ease of placement and retrieval makes them a frequently used tool in interventional radiology. When conventional methods of retrieval fail, the operator must use creative means to extract the filter. Failure of retrieval is associated with a longer dwell time, more transverse tilt, and the presence of an embedded hook (1-4). A variety of advanced techniques have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The possible advantages of the bidirectional sling technique are strengthening of traction/ countertraction force and prevention of potential complications like caval wall dissection and intussusception. 9) Ross et al 10) reported the same concept using the bidirectional approach and emphasized the advantage of making a loop snare from both sides by maximizing axial stability. They also stressed second loop snare was able to strip the leg anchors from the caval wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible advantages of the bidirectional sling technique are strengthening of traction/ countertraction force and prevention of potential complications like caval wall dissection and intussusception. 9) Ross et al 10) reported the same concept using the bidirectional approach and emphasized the advantage of making a loop snare from both sides by maximizing axial stability. They also stressed second loop snare was able to strip the leg anchors from the caval wall.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we believe this could provide more chance of retrieval success by increasing traction/countertraction force by pulling IVCF from both sides. Also, Ross et al 10) described this technique as a last resort because the presence of multiple wires and points of attachment creates an environment that risks entanglement of wires. However, we would like to propose that this technique is easily added in the middle of a procedure any time when we feel more powerful traction force is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Several unconventional techniques, such as loop-snare technique and use of endobronchial forceps, have been described [5,6]. However, most of these advanced techniques are designed for cone-shaped tilted or tip-embedded filters.…”
Section: Introductionmentioning
confidence: 99%
“…The desire to retrieve filters has led to the development and use of various advanced retrieval techniques to increase the retrieval success rate. Several unconventional techniques, such as loop-snare technique and use of endobronchial forceps, have been described [ 5 , 6 ]. However, most of these advanced techniques are designed for cone-shaped tilted or tip-embedded filters.…”
Section: Introductionmentioning
confidence: 99%